Here is the explicit formula for a sequence:

[tex]\[ f(n) = 70(-2)^{n-1} \][/tex]

Which recursive formula can be used to define this sequence for [tex]\( n \ \textgreater \ 1 \)[/tex]?

[tex]\[ \begin{array}{c|l}
\text{A.} & f(n) = 70 f(n-1) \\
\text{B.} & f(n) = f(n-1) - 2 \\
\text{C.} & f(n) = f(n-1) + 70 \\
\text{D.} & f(n) = -2 f(n-1)
\end{array} \][/tex]



Answer :

Let's analyze the given explicit formula for the sequence:

[tex]\[ f(n) = 70(-2)^{n-1} \][/tex]

We want to convert this explicit formula into a recursive formula, which means expressing [tex]\( f(n) \)[/tex] in terms of [tex]\( f(n-1) \)[/tex].

First, let's observe the pattern:

- The first term [tex]\( f(1) \)[/tex] when [tex]\( n = 1 \)[/tex] is:
[tex]\[ f(1) = 70(-2)^{1-1} = 70(-2)^0 = 70 \cdot 1 = 70 \][/tex]

- The second term [tex]\( f(2) \)[/tex] when [tex]\( n = 2 \)[/tex] is:
[tex]\[ f(2) = 70(-2)^{2-1} = 70(-2)^1 = 70 \cdot (-2) = -140 \][/tex]

- The third term [tex]\( f(3) \)[/tex] when [tex]\( n = 3 \)[/tex] is:
[tex]\[ f(3) = 70(-2)^{3-1} = 70(-2)^2 = 70 \cdot 4 = 280 \][/tex]

- The fourth term [tex]\( f(4) \)[/tex] when [tex]\( n = 4 \)[/tex] is:
[tex]\[ f(4) = 70(-2)^{4-1} = 70(-2)^3 = 70 \cdot (-8) = -560 \][/tex]

Now, let's analyze the relationship between consecutive terms. We notice that:

[tex]\[ \begin{aligned} f(2) &= -2 \cdot f(1) & = -2 \cdot 70 & = -140 \\ f(3) &= -2 \cdot f(2) & = -2 \cdot (-140) & = 280 \\ f(4) &= -2 \cdot f(3) & = -2 \cdot 280 & = -560 \end{aligned} \][/tex]

Therefore, we can see a clear pattern where each term is obtained by multiplying the previous term by -2.

Thus, the recursive formula for [tex]\( n > 1 \)[/tex] is:

[tex]\[ \begin{aligned} f(1) &= 70 \\ f(n) &= -2 \cdot f(n-1) \quad \text{for} \quad n > 1 \end{aligned} \][/tex]

From the given choices, the correct recursive formula is:

[tex]\[ f(n) = -2 \cdot f(n-1) \quad \text{for} \quad n > 1 \][/tex]

Hence, the correct answer is:

[tex]\[ f(n) = -2 f(n-1) \][/tex]

Other Questions